La cara norte del corazón - Redondo, Dolores 1969- (Ediciones Destino, 2019)
"In August 2005, a young twenty-five-year-old Amaia Salazar, detective inspector of the Foral Police in Navarra, participates in an exchange programme for Europol police officers at the FBI Academy in the United States, taught by Aloisius Dupree, the head of the research unit. One of the tests consists of studying the real-life case of a serial killer, whom they call "the composer", who always strikes during great natural disasters attacking entire families and leaving an almost liturgical scene behind. Amaia will unexpectedly become part of the research team, which will take them to New Orleans, on the eve of the Katrina hurricane, to try to get ahead of the killer... But a call from her aunt Engrasi in Elizondo will awaken in Amaia old ghosts from her childhood that can change everything, exposing herself, once again, to the north face of the heart."--https://www.pontas-agency.com/the-north-face-of-the-heart-by-dolores-redondo-hits-the-bookstores-as-a-hurricane
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Detective and mystery stories, Spanish; Cuentos policiacos españoles; Policia / Novela; Asesinato / Investigaciones (Pesquisas) / Novela; Secretos / Novela; Detective and mystery fiction; Novels